Tissue engineering human small-caliber autologous vessels using a xenogenous decellularized connective tissue matrix approach: preclinical comparative biomechanical studies - Heine, Jörg; Schmiedl, Andreas; Cebotari, Serghei; Karck, Matthias; Mertsching, Heike; Haverich, Axel; Kallenbach, Klaus (Artificial organs, 2011)
Suggesting that bioartificial vascular scaffolds cannot but tissue-engineered vessels can withstand biomechanical stress, we developed in vitro methods for preclinical biological material testings. The aim of the study was to evaluate the influence of revitalization of xenogenous scaffolds on biomechanical stability of tissue-engineered vessels. For measurement of radial distensibility, a salt-solution inflation method was used. The longitudinal tensile strength test (DIN 50145) was applied on bone-shaped specimen: tensile/tear strength (SigmaB/R), elongation at maximum yield stress/rupture (DeltaB/R), and modulus of elasticity were determined of native (NAs; n = 6), decellularized (DAs; n = 6), and decellularized carotid arteries reseeded with human vascular smooth muscle cells and human vascular endothelial cells (RAs; n = 7). Radial distensibility of DAs was significantly lower (113%) than for NAs (135%) (P < 0.001) or RAs (127%) (P = 0.018). At levels of 120 mm Hg and more, decellularized matrices burst (120, 160 [n = 2] and 200 mm Hg). Although RAs withstood levels up to 300 mm Hg, ANOVA revealed a significant difference from NA (P = 0.018). Compared with native vessels (NAs), SigmaB/R values were lower in DAs (44%; 57%) (P = 0.014 and P = 0.002, respectively) and were significantly higher in RAs (71%; 83%) (both P < 0.001). Similarly, DeltaB/R values were much higher in DAs compared with NAs (94%; 88%) (P < 0.001) and RAs (87%; 103%) (P < 0.001), but equivalent in NAs and RAs. Modulus of elasticity (2.6/1.1/3.7 to 16.6 N/mm2) of NAs, DAs, RAs was comparable (P = 0.088). Using newly developed in vitro methods for small-caliber vascular graft testing, this study proved that revitalization of decellularized connective tissue scaffolds led to vascular graft stability able to withstand biomechanical stress mimicking the human circulation. This tissue engineering approach provides a sufficiently stable autologized graft.